2011
DOI: 10.1177/1740774510396742
|View full text |Cite
|
Sign up to set email alerts
|

Impact and costs of targeted recruitment of minorities to the National Lung Screening Trial

Abstract: Background To promote results in the National Lung Screening Trial (NLST) that are generalizable across the entire US population, a subset of NLST sites developed dedicated strategies for minority recruitment. Purpose To report the effects of targeted strategies on the accrual of underrepresented groups, to describe participant characteristics, and to estimate the costs of targeted enrollment. Methods The 2002–2004 Tobacco Use Supplement was used to estimate eligible proportions of racial and ethnic catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 9 publications
1
65
0
Order By: Relevance
“…32,79 One such intervention targeted minority recruitment using strategic planning, which included meetings and conferences with key stakeholders and minority organizations as a means to increase minority enrollment. 79 The authors examined institutions that employed these strategies and those that did not, and they found a significant increase in the rate of minority accrual in institutions that implemented strategic planning compared with those that did not. 79 This effort suggests that the mistrust of the medical system seen among minority patients might be addressed with culturally sensitive and open community engagement.…”
Section: Individual-level Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…32,79 One such intervention targeted minority recruitment using strategic planning, which included meetings and conferences with key stakeholders and minority organizations as a means to increase minority enrollment. 79 The authors examined institutions that employed these strategies and those that did not, and they found a significant increase in the rate of minority accrual in institutions that implemented strategic planning compared with those that did not. 79 This effort suggests that the mistrust of the medical system seen among minority patients might be addressed with culturally sensitive and open community engagement.…”
Section: Individual-level Barriersmentioning
confidence: 99%
“…79 The authors examined institutions that employed these strategies and those that did not, and they found a significant increase in the rate of minority accrual in institutions that implemented strategic planning compared with those that did not. 79 This effort suggests that the mistrust of the medical system seen among minority patients might be addressed with culturally sensitive and open community engagement.…”
Section: Individual-level Barriersmentioning
confidence: 99%
“…1,[3][4][5][6][7] Despite the literature emphasizing these deficits, African Americans continue to be a disproportionately underrepresented population in cancer clinical trials. [12][13][14][15][16][17][18][19] Research studies often report health disparities as numerical values of cancer cases, cancer deaths, participation or nonparticipation in clinical trials, income level, education level, gender, and reported age groups. [12][13][14][15][16][17][18][19] These are meaningful data that need to be incorporated as part of 34 ADVANCES IN NURSING SCIENCE/JANUARY-MARCH 2014 a strategy to improve recruitment of African Americans to clinical trials.…”
Section: Barriers To Participation and Recruitmentmentioning
confidence: 99%
“…[8] Some of the identified barriers include transportation, childcare, cultural and language differences, inflexible work hours, communication barriers, [13] distrust in health-related research, and less reliable contact information. [8, 10; 1417] …”
Section: Introductionmentioning
confidence: 99%